Nadezhda Tarancheeva, about myself - Terbish, Baasanjav (Kalmyk Cultural Heritage Documentation Project, University of Cambridge, 2019)
Nadezhda talks about herself, her family, Siberian exile, and her work at the National Museum of Kalmykia: I never saw my uncle, but I knew that he had a son and a daughter. The son went missing during World War Two. My uncle worked for the zaisang Lapin as his key keeper or manager. It was the zaisang who sent my father to Paris to learn cooking. In 1942 our place was occupied by the Germans. In early 1943, when our area was liberated by the Red Army, my uncle, along with other people, was tasked with driving livestock from Kalmykia to Salsk. On the way, they came under German bombardment. The livestock ran away, and many people, including my uncle, died. My eldest brother Erenzhen, born in 1921 and who studied law in Pyatigorsk, returned from the war wounded. On 28 December 1943 we were all sent to exile in Siberia. There, my cousins felled trees. Once they had an accident during which one was crushed to death and the other seriously injured her leg. She suffered with her leg her whole life. In 1944 our father died of typhus. In the same year, two of my nephews also died, after eating poisonous mushrooms. In 1946 I started to work in a factory in the city of Zaozernoye in Krasnoyarsk krai. We worked in harmful conditions, and today no one who worked there with me is alive. When Kalmyks were allowed to return to Kalmykia, I settled in Bashanta. In 1964 I joined the Communist Party and worked as a seamstress. Afterwards, I was sent away as a member of Komsomol to organize work at a brick factory. In 1970 I got married and moved to the village of Godzhur. When I worked at the National Museum, people used to bring me relics, including Buddhist sutras. Once the correspondent Alexandra Burataeva brought to our museum a large number of Buddhist statues and paintings that belonged to a Jewish doctor who lived in Kalmykia. After Kalmyks were deported to Siberia, he set out to collect old Kalmyk statues and objects. Whatever people gave us, we accepted with gratitude. Sponsored by Arcadia Fund, a charitable fund of ...